Nutritional and Biochemical Parameters of Honey Contaminated with Insecticide Residues in Male Albino Rats - Osfor, Mostafa M.H.; Ashshi, Ahmed M.; El-Sawy, Naser A.; Alkushi, Abdullah G.; Qusty, Naeem F.H.; Bakr, El-Sayed H.; Hijazi, Haifa M.H.; El-Nabarawy, Ibrahim M. (Pakistan Journal of Nutrition, 2016)
The effect of insecticides contaminating honey on nutritional and biochemical parameters were investigated in male albino rats. Administration of honey containing malathione and dimethoate at levels of 0.003±0.24 and 0.006±0.02 ppm, respectively, significantly decreased body weight of the animals. These levels also significantly decreased the weight of testis, epididymis and suprarenal gland, while it significantly increased the weight of the parenchymatous organs (heart, liver, kidney and spleen). Serum levels of triglycerides, albumin, total protein, alanine transaminase (ALT), creatinine and bilirubin were significantly increased, while there were non-significant differences in levels of cholesterol, aspartate transaminase (AST), alkaline phosphatase (AP), urea and glucose. These results suggest that further studies should be conducted on various nutritional, biochemical, physiological, hormonal and immunological parameters to confirm the adverse impact of insecticide contaminated honey on animals and humans. Moreover, intensive studies are required on the types and levels of honey flavonoids and their impact against harmful action of the insecticides. Additional studies should also be conducted on different vegetables and fruits that could be contaminated with different insecticides and other contaminants.